USE OF VIDEO IN MULTIMEDIA ELECTRONIC EDUCATIONAL RESOURCES (Journal of Information Technologies in Education (ITE), 2015)
The widespread introduction of electronic educational resources in the educational processrequires the development of a scientific basis for all aspects related to their creation and use.These modern means are designed not just to convey to learners the required course material, butalso to create conditions for its most effective study. This is possible in conditions of reasonableapproach to the presentation of educational material on the screen.The article is devoted to consideration of the problem of presenting educational material inelectronic educational resources. Visuals are powerful didactic tool that enhances the perceptionand understanding of educational information. Particular attention is paid to the use of such apowerful medium like video. Investigated the role and importance of video in the learningprocess, their educational opportunities and benefits. Shows types of video and their use inelectronic educational resources. Grounded requirements for training videos. Therecommendations are given on the use of video in combination with other media in electroniceducational resources. Adduced the example a real electronic multimedia educational resourceand shows the possibility of using video.
Keywords: video; multimedia; multimedia educational content; electronic educational resources